Linear quadratic regulator and pole placement for stabilizing a cart inverted pendulum system - Mila Fauziyah; Zakiyah Amalia; Indrazno Siradjuddin; Denda Dewatama; Rendi Pambudi Wicaksono; Erni Yudaningtyas (Bulletin of Electrical Engineering and Informatics, 2020)
The system of a cart inverted pendulum has many problems such as  nonlinearity, complexity, unstable, and underactuated system. It makes this system be a benchmark for testing many control algorithm. This paper  presents a comparison between 2 conventional control methods consist of a linear quadratic regulator (LQR) and pole placement. The comparison  indicated by the most optimal steps and results in the system performance  that obtained from each method for stabilizing a cart inverted pendulum system. A mathematical model of DC motor and mechanical transmission are included in a mathematical model to minimize the realtime implementation problem. From the simulation, the obtained system performance shows that each method has its advantages, and the desired pendulum angle and cart position reached.